2015
DOI: 10.1016/j.drudis.2014.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Targeting xenobiotic receptors PXR and CAR in human diseases

Abstract: Nuclear receptors such as the pregnane X receptor (PXR) and constitutive androstane receptor (CAR) are xenobiotic receptors regulating not only drug metabolism and disposition but also various human diseases such as cancer, diabetes, inflammatory disease, metabolic disease and liver diseases, suggesting that PXR and CAR are promising targets for drug discovery. Consequently, there is an urgent need to discover and develop small molecules that target these PXR- and/or CAR-mediated human-disease-related pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 100 publications
(142 reference statements)
0
89
1
Order By: Relevance
“…Clinical studies showed that the anti‐epileptic drug phenobarbital can activate PXR/CAR. Phenobarbital improved insulin resistance by suppressing gluconeogenesis through CAR, whereas a PXR agonist might impair glucose tolerance in healthy volunteers receiving rifampicin 85. However, separating out the beneficial metabolic effects from the adverse effects is challenging.…”
Section: Nuclear Receptors As Therapeutic Targetsmentioning
confidence: 99%
“…Clinical studies showed that the anti‐epileptic drug phenobarbital can activate PXR/CAR. Phenobarbital improved insulin resistance by suppressing gluconeogenesis through CAR, whereas a PXR agonist might impair glucose tolerance in healthy volunteers receiving rifampicin 85. However, separating out the beneficial metabolic effects from the adverse effects is challenging.…”
Section: Nuclear Receptors As Therapeutic Targetsmentioning
confidence: 99%
“…tuberculosis infection and rifampicin treatment modulates the macrophage drug efflux potential by modulating the ABC transporters expression through xenobiotic nuclear receptor-As stated above PXR and CAR are known to regulate the expression of drug efflux transporters and rifampicin is known to activate both PXR and CAR (19). Also, activated PXR and CAR leads to induction of a set of overlapping target genes (20). Therefore, we investigated the role of PXR and CAR in modulating the macrophage efflux transporter expression induced by M. tuberculosis infection and by rifampicin treatment.…”
Section: Expressionmentioning
confidence: 99%
“…Biologically, RXR serves an important role via its potent ability to associate with a variety of nuclear receptors. RXR possesses the ability to modulate nutrient metabolism via forming so-called 'permissive' heterodimers with PPAR (peroxisome proliferator-activated receptor), the liver-X-receptor (LXR), the farnesoid X receptor (FXR), the pregnane X receptor (PXR) and the constitutive androstane receptor (CAR), of which all of them start being functional, when ligands are associated to one or both of these heterodimers [10][11][12][13].…”
Section: Vitamin K2 -Vital For Health and Wellbeingmentioning
confidence: 99%
“…Recently, it was revealed that SXR (most unexpectedly so) in fact makes a major contribution to (1) subduing inflammation, (2) bone homeostasis, (3) vitamin D turnover, (4) lipid metabolism, (5) energy homeostasis, as well as (6) the body's defence against cancer. Hence, the discovery of SXR as more than a xenobiotic sensor enables the use of a powerful tool for scrutinizing new mechanisms via which dietary factors, chemicals and the environment ultimately impact health, as well as disease development, prevention and treatment [10][11][12][13].…”
Section: Vitamin K2 -Vital For Health and Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation